2021
DOI: 10.2106/jbjs.20.01152
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Comorbidities and Complications Using ICD-9 and ICD-10 in Total Hip and Knee Arthroplasties

Abstract: Background: The transition to the new ICD-10 (International Classification of Diseases, Tenth Revision) coding system in the U.S. poses challenges to the ability to consistently and accurately measure trends in comorbidities and complications. We examined the prevalence of comorbidities and postoperative medical complications before and after the transition from ICD-9 to ICD-10 among patients who underwent primary total hip or knee arthroplasty (THA or TKA). We hypothesized that the transition to I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…These findings were likely just the result of a changing definition for a complication, but the study demonstrated that the transition from the ICD-9 to the ICD-10 introduced a discontinuity in the data that can result in an artificial change in the reported prevalence of a given complication. These findings also have been documented in relation to the prevalence of comorbidities in patients who undergo TJA due to changes in the coding system 19 . Changes to administrative claims coding are not limited to major transitions, such as the switch from the ICD-9 to the ICD-10, because there are often changes to the definitions for CPT codes or the introduction of new CPT codes, which occur more frequently 21,22 .…”
Section: Pitfalls Of Coding In Databasesmentioning
confidence: 77%
See 2 more Smart Citations
“…These findings were likely just the result of a changing definition for a complication, but the study demonstrated that the transition from the ICD-9 to the ICD-10 introduced a discontinuity in the data that can result in an artificial change in the reported prevalence of a given complication. These findings also have been documented in relation to the prevalence of comorbidities in patients who undergo TJA due to changes in the coding system 19 . Changes to administrative claims coding are not limited to major transitions, such as the switch from the ICD-9 to the ICD-10, because there are often changes to the definitions for CPT codes or the introduction of new CPT codes, which occur more frequently 21,22 .…”
Section: Pitfalls Of Coding In Databasesmentioning
confidence: 77%
“…Following the transition to the ICD-10, each specific complication has a separate code to designate the joint and laterality of the complication (e.g., ICD-10 T84.033: Mechanical loosening of internal left knee prosthetic joint). Although this transition brought much-needed specificity in TJA documentation, research has demonstrated that the transition to the ICD-10 significantly altered the reported prevalence of common surgical complications following TKA and total hip arthroplasty (THA) 19,20 . These findings were likely just the result of a changing definition for a complication, but the study demonstrated that the transition from the ICD-9 to the ICD-10 introduced a discontinuity in the data that can result in an artificial change in the reported prevalence of a given complication.…”
Section: Pitfalls Of Coding In Databasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Data from 2004 to 2020 were used to describe trends in insurance type. Only data from 2015 to 2020 were used for statistical analysis given the transition from ICD-9 to ICD-10 that occurred during 2015, which led to differences in the reported rates of comorbidities and complications between these 2 ICD systems 10,11 .…”
Section: Methodsmentioning
confidence: 99%
“…Time from discharge to readmission was reported as the number of days from the discharge date and the date of the first readmission. Readmissions registered with a diagnosis code previously associated with arthroplasty complications were also registered as complications [12,13] (Table 2, see Appendix). Readmissions less than 4 hours after discharge from the primary surgical admission were not considered readmissions.…”
Section: Outcome Measuresmentioning
confidence: 99%